Pengaruh Karakteristik Petani terhadap Pengetahuan Inovasi Budidaya Cengkeh di Kabupaten Halmahera Timur - Setiyowati, Tri; Fatchiya, Anna; Amanah, Siti (Jurnal Penyuluhan, 2022)
The innovation adoption process begins with the knowledge stage. At the stage of knowledge is influenced by individual characteristics. This study aims to determine the distribution of farmer characteristics and analyze the effect of characteristics on farmer knowledge. The study using the census method (140 clove farmers) was conducted in East Halmahera Regency. Interviews and observations were conducted to obtain data on individual characteristics. Simple linear regression analysis was used to analyze the data. The results showed that the age of the farmer was in the middle adult category with clove farming experience between 11-20 years. The level of formal education is in the low category, the level of cosmopolitan of farmers is low with a narrow land area and has a low level of income. However, the motivation of farmers in clove farming is included in the medium category. Individual characteristics of farmers who have a significant influence are cosmopolitan and income levels, while land area has a negative influence.